How to do the work : recognize your patterns, heal from your past, and create your self - LePera, Nicole (Harper Wave, an imprint of HarperCollinsPublishers, 2021)
"From Dr. Nicole LePera, creator of "the holistic psychologist"-the online phenomenon with more than 2M followers on Instagram-comes a revolutionary approach to self-improvement, integrating the tools of various modalities and disciplines with traditional psychology to offer a practical program that guides readers to create radical change"--